An analysis of strain localization and formation of face wrinkles in edge-wise loaded corrugated sandwich panels using a continuum damage model. (15th March 2015) - Åslund, Pär E.; Hägglund, Rickard; Carlsson, Leif A.; Isaksson, Per
Abstract: This paper examines the compressive failure mechanism in edge-to-edge loaded corrugated sandwich panels. The formation of face wrinkles is specifically considered. A detailed finite element model of face sheets and web core of a sandwich panel was developed to provide insight on the failure mechanism. A gradient enhanced continuum damage theory was implemented to capture length effects caused by the material microstructure including formation of damage in the face sheets and core. Distributions of strains in the face sheets determined from finite element analysis (FEA) are compared to experimentally measured strains. The predicted location and orientation of the face wrinkle, as indicated by high values of the second principal strain, agrees well with experimental observations. Load vs. out-of-plane deflection curves obtained from FEA with the gradient enhanced damage material model are compared to those obtained from a linear-elastic material model and experimentally determined curves. The gradient enhanced solution gives qualitatively better agreement with experimental results, although the magnitudes of strains are less than those determined experimentally.